Semantics of Neologisms in Modern Linguistics (Eurasian Scientific Herald, 2022)
This article is about neologisms. Neologism is a new word. With the development of society, culture, the creation of new technology, tools, the formation of new ideas about the world, new objects and concepts appear that require designation in words.